Relationship Between Morphological Characteristics and Dynamic Running Parameters in the Case of Boys Aged 10-12 years - Slavenko Likic; Izet Bajramovic; Damira Vranesic-Hadzimehmedovic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of the research is to determine the relationship between morphological characteristics and dynamic parameters of running in the case of boys aged 10-12 years. The study was conducted on a sample of 75 respondents, who are separated from the fourth-grade elementary school population. Morphological characteristics are measured by a set of fifteen variables: longitudinal dimensionality (3 variables), transversal dimensionality (4 variables), volume and body mass (4 variables), fatt tissue (4 variables), and body mass index. Dynamic parameters of running were estimated by measuring the passing time at 5m segments of the whole distance. Variables of dynamic running parameters have achieved statistically significant correlation with variables of transversal dimensionality, volume and body mass and fat tissue (p<0.05). Also, statistically significant correlation (p<0.01) of mean intensity was obtained between body mass index and all variables of dynamic running parameters. Based on the results of dynamic running parameters it can be concluded that the analyzed sample of boys aged 10-12 years is characterized by the following pattern of running structure at 50 meters: the acceleration phase lasts from the start to the fifteen meters section; stable running phase lasts from 15 to 40 meters, indicating that the maintenance length of the maximum speed level is 25 meters; and the deceleration phase of running lasts from 40 to 50 meters.